2018
DOI: 10.3390/rs10071153
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gap Fraction and Foliage Clumping in Forest Canopies

Abstract: The gap fractions of three mature hemi-boreal forest stands in Estonia were estimated using the LAI-2000 plant canopy analyzer ( LI-COR Biosciences, Lincoln, NE, USA) , the TRAC instrument (Miami, FL, USA), Cajanus’ tube, hemispherical photos, as well as terrestrial (TLS) and airborne (ALS) laser scanners. ALS measurements with an 8-year interval confirmed that changes in the structure of mature forest stands are slow, and that measurements in the same season

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additional problems might also appear when a laser beam hits a canopy object, because the strength of the reflected signal depends on several factors that includes the reflection coefficient, surface roughness, the incidence angle and the fraction of the pulse cross section covered by the target [30]. As a result, it seems the edge of the canopy objects will lack of laser returns and assumed as gaps in the angular grid.…”
Section: Angular Resolution and Gfmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional problems might also appear when a laser beam hits a canopy object, because the strength of the reflected signal depends on several factors that includes the reflection coefficient, surface roughness, the incidence angle and the fraction of the pulse cross section covered by the target [30]. As a result, it seems the edge of the canopy objects will lack of laser returns and assumed as gaps in the angular grid.…”
Section: Angular Resolution and Gfmentioning
confidence: 99%
“…TLS can estimate GF on discrete periods of time [18,28,30], and also employed to continuously monitor the canopy structure dynamics [31,32]. Consequently, TLS provides a non-destructive alternative to measure GF that is independent from natural light conditions [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap fraction t(θ) can be calculated as a ratio from the below-and above-canopy radiation measurements (Welles & Norman, 1991) using plant canopy analysers. Kuusk et al (2018) showed that substantial discrepancies exist between estimates of t(θ) when using different optical methods. Cescatti (2007) published the LinearRatio method and showed how to use two digital hemispherical cameras as a pair of plant canopy structure analyser devices.…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al [2], in turn, introduce the first in situ continuous measurements of canopy scale (overstory + understory) and understory spectral reflectance and vegetation index in an open boreal forest in interior Alaska. Kuusk et al [3] offer the most comprehensive comparison of different instruments and methods for estimating the gap fraction of (hemi-)boreal canopies to date. Oveland et al [4] compare both the accuracy and efficiency of three different ground-based laser scanning methods (terrestrial laser scanner, handheld laser scanner and a backpack laser scanner) for tree stem detection in southeastern Norway.…”
mentioning
confidence: 99%